Value Relevance of Accounting Information and The Pricing of Indonesian Initial Public Offerings - Tatang Ary Gumanti (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to examine the relation between accounting measures of total firm risk and the value of firms making initial public offerings (IPOs). The existing explanations of the pricing of IPOs suggest that the value of IPOs is related to a number of fundamental accounting variables of the firms. A sample of 149 Indonesian IPO firms that went public during the period 1989-1997 is examined and is used to test the null hypothesis that the IPO’s price is not related to firm specific accounting risk measures.The results provide evidence that the IPOs’ accounting information is value relevant to the market price of the IPO. Earnings Per Share (EPS), Book Value of Equity (BVE), and financial leverage are significantly related to the level of offering price. The study concludes that the IPOs’ accounting information is value relevant about the offer and market prices of the IPO, which is in support to that of Kim et al. (1995) and Klein (1996).